Updating, subtyping, and perceptions of the police: Implications of police contact for youths’ perceptions of procedural justice - Dan-Irabor, Dale (Criminology, 2023)
Individuals enter police encounters with expectations about how these interactions will unfold. These expectations are often rooted in racialized personal, vicarious, and collective experiences with the police. Bayesian updating posits that the way youth perceive treatment by the police during stops and arrests combines with prior expectations and perceptions to shape current views of the law, whereas subtyping suggests this process differs by race. This study examines intra- and interracial variability in these processes using longitudinal survey data from 3,085 Black and White youth. Regardless of race, youth who indicate they were treated with disrespect during police encounters had lower perceptions of procedural justice than did those with no contact, whereas contact perceived as respectful had no significant effects. For White but not Black youth, police encounters rated as "neutral" are associated with more negative views of the police. Other forms of legal socialization are also racialized, including messages conveyed in the media and by parents. Limited evidence exists that prior views of the police moderate the effect of police encounters on procedural justice or that these conditioning effects vary by race. Findings support updating, but race differences do not neatly align with findings expected with updating or subtyping theory.